'Ilmu Al-Lughah Al-Ijtima'ī wa Ta'lim al-Lughah Al-‘Arabīyah li Al-Nātiqīn bi Ghayrihā - Ahmad Ubaedi Fathudin (ALSINATUNA, 2016)
Language learning cannot work without integrating other fields of knowledge such as psychology, anthropology, sociolinguistics, etc. Sociolinguistics is a branch of linguistics which discusses about language due to social factors. It has an important role in language learning especially in making it easily understandable for the language learners by understanding the language use of the native speakers. The contribution of sociolinguistics in Arabic language learning for foreign language learners can be seen from the relationship between language and social environment. In this case, it does not only learn about the elements or internal systems of Arabic language such as phonology, syntax, and morphology, but also the social context such as speech community, social class, language use and culture. It means sociolinguistics gives information about the definition and use of Arabic language based on the social context.